The Effect of Curing Time on the Impact Strength of Resin Denture Bases Made by 3D Printing Techniques - Putra, Kriswandy; Fransisca, Wennie; Tambunan, Nur Aini Putri Nauli Br (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
Advances in additive manufacturing have enabled the fabrication of denture bases using three-dimensional (3D) printing technology; however, the mechanical properties of the resulting materials, particularly impact strength, are highly influenced by post-processing parameters such as curing time. This experimental laboratory study aimed to evaluate the effect of different curing time variations on the impact strength of 3D-printed denture base resin and to compare its performance with that of heat-polymerized acrylic resin (HPAR). A post-test only control group design was employed, in which specimens were divided into four groups consisting of 3D-printed resin with curing times of 4.5, 5.0, and 5.5 seconds, and a control group fabricated from HPAR. The results demonstrated that the 3D-printed resin cured for 5.0 seconds exhibited the highest mean impact strength (1.56 ± 0.14 kJ/m²), followed by the 4.5-second group (1.47 ± 0.09 kJ/m²), while the lowest value was observed in the 5.5-second curing group (1.28 ± 0.23 kJ/m²). In contrast, the HPAR group showed substantially higher impact strength than all 3D-printed resin groups, with a mean value of 2.99 ± 0.97 kJ/m². These findings indicate that curing time optimization significantly affects the impact strength of 3D-printed denture base resin; nevertheless, heat-polymerized acrylic resin remains superior in terms of mechanical toughness for denture base applications